KEWENANGAN DPD DALAM PENYUSUNAN UNDANG-UNDANG - Caka Bawa, I Putu Gede; Anom Pemayun, Tjokorde Istri (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 07, November 2013, 2013)
The 1945 constitution of tye republic of Indonesia (hearnaftor the constitution) be for imandementexplacitysatate regarding Indonesia as the shite basldan the rule of Law. On the country it was ligitiondes by parlementerfoorprocusted by make the legislafion for DPD so DPR for the law make building foor the outonome (cheek and bafanees) or DPD, DPR, buy, Regulation foorbugeter (APBN) and (Religius) foor.After the Amandement the Constitution head been for Supranady of Law, make buy parlement to building foor, the will foe state goedgornementsee and visitionfoorwellfor state in Indonesia by Legislation Regulation by the Parlement more over it is contray the spirit of the Law number 32 year 2004 Reguling Local Distriet Autonomy that will state in its. Consideration us specially by vision ad mission program bye the Regional how of Refrentationso make good government local otonom by the Transpiration, Akuntablety and Responsibility by the Parlement.
Keywords: Authority of the DPD, making, Act